Effects of short-term sled towing and unloaded sprint training on leg power and stiffness - Alcaraz, P.; Elvira, J.; Palao, J.; Palao, V.; Avila, V. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The relationship between stiffness and athletic performance is of great interest to the sport and research communities. Unfortunately, there are no longitudinal studies that have investigated the effects of strength or power training on mechanical stiffness in sprinters. The aim of the study was to examine the effect of resisted and unloaded sprint training programs on sprint time, leg power, and stiffness.